1991
DOI: 10.1128/jb.173.3.997-1003.1991
|View full text |Cite
|
Sign up to set email alerts
|

Velocity changes, long runs, and reversals in the Chromatium minus swimming response

Abstract: The velocity, run time, path curvature, and reorientation angle of Chromatium minus were measured as a function of light intensity, temperature, viscosity, osmotic pressure, and hydrogen sulfide concentration. C. minus changed both velocity and run time. Velocity decreased with increasing light intensity in sulfide-depleted cultures and increased in sulfide-replete cultures. The addition of sulfide to cultures grown at low light intensity (10 microeinsteins m-2 s-1) caused mean run times to increase from 10.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…Thereafter, cells reoriented randomly, and resumed forward swimming. We observed a different motile behavior for M. gracile, a finding consistent with the observation made for Allochromatium vinosum by Mitchell et al (29).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thereafter, cells reoriented randomly, and resumed forward swimming. We observed a different motile behavior for M. gracile, a finding consistent with the observation made for Allochromatium vinosum by Mitchell et al (29).…”
Section: Discussionsupporting
confidence: 81%
“…The motile behavior of M. gracile can generally be described as a random walk (2,29). Intervals of straight swimming paths are interrupted by stops, followed by a reversal in swimming direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the only other comparable study on the effect of viscosity on locomotory velocity at low Re, Mitchell et al (1991) reported that water viscosity accounted for only 26% of the decline in swimming velocity of the purple sulphur bacterium Chromatium minus over a 30°C temperature drop (from 45 to 15OC). The increase in viscosity over this temperature range is far greater than that in either this study or that of Podolsky & Emlet (1993), and raises the question of why viscosity seems to play such a relatively minor role in locomotory kinetics of C. minus (26 %) compared to the larvae of Dendraoter excentricus (40%) and Galeolaria caespitosa (46%).…”
Section: Swimming Velocitymentioning
confidence: 96%
“…The video image was recorded continuously by a video camera (FCD-725; Ikegami Co.) and a video cassette recorder (BR9000; Hitachi Co.). Run times were measured as previously described (14). Measurements were made on the monitor screen by stretching plastic wrap flat against the screen surface and following a cell with a permanent marking pen.…”
Section: Methodsmentioning
confidence: 99%